(untitled) (Economics and region, 2025)
The article examines the peculiarities of labor organization at Ukrainian enterprises in the conditions of martial law, which were caused by the military conflict. The analysis focuses on new challenges faced by enterprises, namely: ensuring the safety of employees, adapting organizational processes to changed working conditions, as well as introducing new forms of work, such as remote and flexible. Considering external and internal threats, enterprises must actively adapt their management structure, communication system and production processes to ensure business continuity and support personnel in crisis. The authors also focus on the impact of military operations on personnel, in particular on the psycho-emotional state of employees, a decrease in motivation and productivity, as well as on the difficulties in ensuring normal working conditions in conditions of high instability. The article indicates the need for psychological support of employees through the creation of special programs aimed at reducing stress and adapting to new conditions. In addition, important aspects of employee safety are considered, in particular, ensuring their working conditions in conditions of increased risks to health and life, as well as the need to create crisis headquarters at enterprises for prompt response to unforeseen situations. The article also offers practical recommendations for improving the organization of work at enterprises in emergency situations, which include optimization of personnel processes, improvement of the system of communication and coordination of actions, as well as adaptation of innovative labor management technologies to increase work efficiency. Given the importance of economic stability and social well-being, the organization of work should be oriented towards ensuring flexibility in the constantly changing conditions of the external environment.